Mental time travel in mild cognitive impairment - Coelho, Sara (2019)
Introduction: Mental Time Travel (MTT) is the people's ability to remember themselves in the past and to imagine themselves in the future, and influence important life domains such as making decisions and planning future actions. It is widely recognized that patients with aMCI have deficits in episodic memory, but they also show impairments in semantic memory. It has been controversial whether MTT tasks are disturbed in aMCI mainly in relation to internal details related to episodic information, or external details, representing semantic and other extraneous information. The present study assessed whether patients with aMCI are affected in MTT regarding generation of internal details and external details, in past and future dimensions. Furthermore, it analyzed production in individual detail categories (internal: event details, thought/emotion, place, time, perceptual; external: extraneous events, semantic, other, repetitions). Method: Twenty-nine patients with aMCI and 29 healthy controls underwent a MTT task based on an Autobiographical Interview, where they had to generate past and future events in response to cue words. Transcriptions were segmented and classified into internal detail categories and external detail categories, and composite scores were obtained. Results: Patients with aMCI could globally produce significantly less details than controls. Similar to controls, patients with aMCI produced more internal details than external details, had more difficulty in generating details regarding the future as compared to the past, and scored higher in the detail categories event details and thought/emotion which represent internal detail types. Conclusions: Patients with aMCI showed widespread deficits in MTT, presumably reflecting deficiencies in the complex and multiple cognitive abilities required for MTT tasks.